Osmotically Enabled Wearable Patch for Sweat Harvesting and Lactate Quantification - Tamoghna Saha; Jennifer Fang; Sneha Mukherjee; Charles T. Knisely; Michael D. Dickey; Orlin D. Velev (Micromachines, 2021)
Lactate is an essential biomarker for determining the health of the muscles and oxidative stress levels in the human body. However, most of the currently available sweat lactate monitoring devices require external power, cannot measure lactate under low sweat rates (such as in humans at rest), and do not provide adequate information about the relationship between sweat and blood lactate levels. Here, we discuss the on-skin operation of our recently developed wearable sweat sampling patch. The patch combines osmosis (using hydrogel discs) and capillary action (using paper microfluidic channel) for long-term sweat withdrawal and management. When subjects are at rest, the hydrogel disc can withdraw fluid from the skin via osmosis and deliver it to the paper. The lactate amount in the fluid is determined using a colorimetric assay. During active sweating (e.g., exercise), the paper can harvest sweat even in the absence of the hydrogel patch. The captured fluid contains lactate, which we quantify using a colorimetric assay. The measurements show the that the total number of moles of lactate in sweat is correlated to sweat rate. Lactate concentrations in sweat and blood correlate well only during high-intensity exercise. Hence, sweat appears to be a suitable biofluid for lactate quantification. Overall, this wearable patch holds the potential of providing a comprehensive analysis of sweat lactate trends in the human body.